Fine Mapping, Candidate Gene Identification and Co-segregating Marker Development for the Phytophthora Root Rot Resistance Gene RpsYD25 - Zhong, Chao; Sun, Suli; Zhang, Xuecui; Duan, Canxing; Zhu, Zhendong (Frontiers in Genetics, 2020)
Phytophthora root rot caused by Phytophthora sojae is a serious diseasesdestructive disease of soybean. The most effective disease-control strategy is to deploy resistant cultivars carrying Rps genes. Soybean cultivar Yudou25 can effectively resist pathogen pathotypes of Phytophthora P. sojae in China. Previous studies have mapped the Rps gene in Yudou25, RpsYD25, on chromosome 3. In this study, at first RpsYD25 was located between SSR markers Satt1k3 (2.2 cM) and BARCSOYSSR_03_0253 (4.5 cM) by using an F2:3 population containing 165 families derived from Zaoshu18 and Yudou25. Then the recombination sites were identified in 1127 F3:4 families derived from Zaoshu18 and Yudou25 using the developed PCR-based SNP, InDel and SSR markers, and RpsYD25 was finely mapped in the a 101.3 kb genomic region. an F2:3 population containing 165 families derived from Zaoshu18 and Yudou25 was used to map the Rps geneconstruct a genetic linkage map for RpsYD25, locating RpsYD25 between SSR markers Satt1k3 (2.2 cM) and BARCSOYSSR_03_0253 (4.5 cM). The 1127 F3:4 families derived from Zaoshu18 and Yudou25 were screened for recombinants using the developed PCR-based SNP, InDel and SSR markers, and the recombination sites of 1127 families were identified. RpsYD25 was mapped in thea 101.3 kb genomic region. In this region, a zinc ion binding and nucleic acid binding gene Glyma.03g034800 03g034700 and two NBS-LRRNBS-LRR genes Glyma.03g034800 and Glyma.03g034900 were predicted as candidate genes of RpsYD25, and five co-segregated SSR markers with RpsYD25 were identified and validated to be diagnostic markers. Combined with the resistance reaction to multiple P. sojae isolates, seven of 178 soybean genotypes were detected to containing RpsYD25 using the five co-segregated SSR markers. The soybean genotypes carrying RpsYD25 and the developed co-segregated markers can be effectively applied in the breeding for P. sojae resistance in China.